Internalizing Social Islamic Character Values (Ukhuwah And Tazkiyah) in Mitigating Student Bullying Behavior at Sdn 40 Bengkulu City - Sutrian Efendi; Bambang Irawan; Luci Lestari; Errick Avra; Sutra Selegar (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The rampant phenomenon of bullying at the elementary school level demands a preventive approach that touches children's spiritual and emotional roots. This study aims to analyze the process of internalizing social Islamic moral values (akhlak sosial), focusing on the concepts of Ukhuwah (brotherhood) and Tazkiyah (purification of the soul), as an instrument to mitigate bullying behavior at SDN 40 Kota Bengkulu. Using a descriptive qualitative approach, data were collected through in-depth interviews with Islamic Education (PAI) teachers, the school principal, and students, as well as through field observations and documentation. The results indicate that the internalization process is carried out through three main stages: value transformation in the classroom, value transaction through interactive discussions, and trans-internalization through the habituation of the school's religious culture. The integration of the Ukhuwah concept successfully fosters empathy among students, while Tazkiyah trains students to control their egos and negative emotions. This study concludes that strengthening spiritual-based social morals is effective in preventively reducing both verbal and physical bullying